Pengaruh digital engagement dan gamifikasi terhadap work engagement karyawan yang bekerja di Jakarta dan Tangerang - Christopher Salim; Aldi Ilham Firdaus; Nopriadi Saputra (Penerbit Goodwood, 2020)
Purpose: The purpose of this study was to determine the level and the effect of digital engagement and gamification on work engagement of employees who work in Jakarta and Tangerang. Research methodology: This research used descriptive, comparative and associative methods. It used primary data through the questionnaire distribution with 401 respondents of employees who work in Jakarta and Tangerang. This study used multiple regression techniques as the data analysis technique. Results: The results of the study indicate that digital engagement has no influence on work engagement, but gamification influences work engagement. Limitations: This research only assessed digital engagement, gamification and work engagement variables, and only employees who work in Jakarta and Tangerang, and there was limited clear literacy of gamification and digital engagement. Contribution: This study shows the level of work engagement, digital engagement and gamification and how digital engagement and gamification affect work engagement. Employers can use this research as consideration to improve their employees work engagement by implementing the concept of gamification and noticing their employee’s level of digital engagement. Keywords: Digital engagement, Gamification, Work engagement